1993
DOI: 10.1126/science.8248779
|View full text |Cite
|
Sign up to set email alerts
|

A Switch Between Two-, Three-, and Four-stranded Coiled Coils in GCN4 Leucine Zipper Mutants

Abstract: Coiled-coil sequences in proteins consist of heptad repeats containing two characteristic hydrophobic positions. The role of these buried hydrophobic residues in determining the structures of coiled coils was investigated by studying mutants of the GCN4 leucine zipper. When sets of buried residues were altered, two-, three-, and four-helix structures were formed. The x-ray crystal structure of the tetramer revealed a parallel, four-stranded coiled coil. In the tetramer conformation, the local packing geometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

80
1,667
6
9

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,475 publications
(1,770 citation statements)
references
References 53 publications
80
1,667
6
9
Order By: Relevance
“…Here we describe the crystal structure of GCN4-pLI in a different spacegroup than originally reported (14) (Figure 1a), and report structures of 11 peptides in the parallel configuration and one peptide in the antiparallel configuration containing hydrophobic core substitutions ( Figure 2, Table 3). All crystals in which peptides adopted the parallel configuration were processed in the P4 1 32 spacegroup, where the four-helix bundle is generated by a crystallographic two-fold symmetry axis acting on the two-strand asymmetric unit, so that 12 four-helix bundles comprise the unit cell contents.…”
Section: Crystal Structuresmentioning
confidence: 95%
See 1 more Smart Citation
“…Here we describe the crystal structure of GCN4-pLI in a different spacegroup than originally reported (14) (Figure 1a), and report structures of 11 peptides in the parallel configuration and one peptide in the antiparallel configuration containing hydrophobic core substitutions ( Figure 2, Table 3). All crystals in which peptides adopted the parallel configuration were processed in the P4 1 32 spacegroup, where the four-helix bundle is generated by a crystallographic two-fold symmetry axis acting on the two-strand asymmetric unit, so that 12 four-helix bundles comprise the unit cell contents.…”
Section: Crystal Structuresmentioning
confidence: 95%
“…Apparent aggregation states (N agg ) were calculated from the elution volume by first using the calibration plot to determine the apparent MW of the bundle, and then dividing this value by the calculated MW of an individual peptide. A control peptide reported to form a coiled-coil trimer in solution (14) had an observed N agg of 3.2.…”
Section: Size Exclusion Chromatographymentioning
confidence: 99%
“…Size exclusion chromatography (SEC) showed that all the peptides were dimers except for 6F, the all-Ala surface sequence, which migrated as a tetramer. These data show that surface redesign did not change the tertiary structure of these peptides, in convast to some core redesigns (Harbury et al, 1993). In addition, nuclear magnetic resonance (NMR) spectra of the peptides at -1 mM showed chemical shift dispersion similar to GCN4-pI (data not shown).…”
Section: Resultsmentioning
confidence: 75%
“…GCN4-pl and p-LI (Harbury et al, 1993) were used as size standards for dimer and tetramer, respectively. Five-pL injections of -1 mM peptide solution were chromatographed at 0.50 mL/min and monitored at 214 nm.…”
Section: Size Exclusion Chromatographymentioning
confidence: 99%
“…18,19 Leucine zippers are short coiled-coil domains that serve to dimerize or oligomerize protein subunits. 20,21 Crystal structural analysis indicates that an ILZ forms trimers through self-assembly. 22 Soluble TNF/ TNF receptor modified by an ILZ motif can form a stable trimeric or multiple oligomerization states.…”
Section: Introductionmentioning
confidence: 99%